2015
DOI: 10.18186/jte.97467
|View full text |Cite
|
Sign up to set email alerts
|

Dye Visualization of a Yawed Slender Delta Wing

Abstract: In the present experimental study, effects of yaw angle, β on the flow structure at high angles of attack, α with 70° sweep angle, Λ were investigated using the dye visualization technique. In the case of zero yaw angle, β a pair of leading edge vortices take place on both sides of cords axis are more or less symmetrical over the delta wing. These symmetrical vortical flow structures start deteriorating when angle yaw, β is introduced. Onset of vortex breakdown location on the windward side occurs further upst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It has been observed that there is no reversed flow zone at α = 25°; however, the reversed flow zone (circulations) takes place at α = 35° when β is higher than 8°. As stated by Karasu, 43 while LEV breakdown occurs at about x/c = 1 at α = 25° and β = 0°, the onset of the breakdown of LEV occurs at about x/c = 0.6 at α = 35° and β = 0°, so one can conclude that if LEV breakdown happens over the wing surface, the reaction of the flow over a delta wing against to β is higher.
Figure 4.Time-averaged streamline, < Ψ >, patterns at α = 25° and 35° for β = 0°, 8°, 12°, and 20°.
…”
Section: Resultsmentioning
confidence: 90%
“…It has been observed that there is no reversed flow zone at α = 25°; however, the reversed flow zone (circulations) takes place at α = 35° when β is higher than 8°. As stated by Karasu, 43 while LEV breakdown occurs at about x/c = 1 at α = 25° and β = 0°, the onset of the breakdown of LEV occurs at about x/c = 0.6 at α = 35° and β = 0°, so one can conclude that if LEV breakdown happens over the wing surface, the reaction of the flow over a delta wing against to β is higher.
Figure 4.Time-averaged streamline, < Ψ >, patterns at α = 25° and 35° for β = 0°, 8°, 12°, and 20°.
…”
Section: Resultsmentioning
confidence: 90%
“…Overall scene of vortex bursting close to the delta wing surface is presented in Figure 3 (Karasu et al, 2015). As seen in the figure, yaw angle, ȕ influences onset of vortex location in dramatically.…”
Section: Fig 1 Types Of Vortex Bursting In a Tubementioning
confidence: 94%
“…In addition to other studies PIV measurement [21] is being provided hydrodynamics of flow structures, domain of the wake region, locations of the singular points, and locations of the peak values of turbul12ence quantities, such as, the concentration of vorticity, Reynolds stresses, velocity fluctuations and turbulent kinetic energy which are substantially affected by the variation of the Reynolds numbers. The presence of a reversed flow in the region of cavities magnifies the level of these flow characteristics when the Reynolds number is increased.…”
Section: Introductionmentioning
confidence: 99%